Observational Analysis of Injury and Head Contact Events in Youth Ice Hockey: Putting Youth Hockey into Context - Laflamme, Yannick (Université d'Ottawa / University of Ottawa, 2018)
Concerns about safety in youth hockey have been openly expressed in public and in academic circles. Sports injury literature continue to report that the prevalence of injury in hockey remains high at both the grassroots and elite levels. Much of this injury reporting, however, utilize injury reporting methods that provide very little about how and why these injuries are occurring. The comprehensive prospective observational approach utilized in this thesis proved most effective in understanding not only injury events and head contact events, but how and why they are taking place throughout the course of a hockey game. Knowing the contextual factors surrounding such events are important in building injury prevention strategies and to minimize all types of head contact. As evidenced in this research, the type of head contact being experienced differs according to age level, which means measures to reduce head contact must be targeted at specific age levels. With this said, given the amount of head contact that was documented throughout all levels of hockey, it does warrant further monitoring of the sport to ascertain the extent to which head trauma is impacting player brain development and to strive further in eliminating head contact altogether.
Keywords: Hockey; Injury; Head contact; Youth; Injury reporting; Bodychecking